2019
DOI: 10.3390/ijms20184470
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Stress-Induced Spermatogenesis Impairment in Male Rats Following Unpredictable Chronic Mild Stress (uCMS)

Abstract: The negative association between psychological stress and male fertility has been known for many years. This study was aimed at (i) identifying spermatogenesis impairment induced by psychological stress in rats and (ii) exploring the role of glucocorticoid receptor (GR) signaling in these adverse effects (if they exist). Male Sprague Dawley rats were exposed to a six-week period of unpredictable chronic mild stress (uCMS) along with cotreatment of GR antagonist RU486 (1 mg/kg/day). Testicular damage was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 45 publications
5
34
0
Order By: Relevance
“…Besides, secondary infertility was significantly higher in patients with posttraumatic stress disorder 56 . Our results showing the inhibitory role of stress hormones on sperm functionality are supported by the data presenting stress-induced-GRs-signaling-mediate spermatogenesis impairment 57 as well as reduced testosterone and sperm motility in high and moderate male runners 58 . Oppositely, in α1-ADRsknockout-male-mice 22 fertility and spermatogenesis are altered, suggesting the important and complex involvement of adrenergic signaling in spermatogenesis and fertility.…”
Section: Discussionsupporting
confidence: 85%
“…Besides, secondary infertility was significantly higher in patients with posttraumatic stress disorder 56 . Our results showing the inhibitory role of stress hormones on sperm functionality are supported by the data presenting stress-induced-GRs-signaling-mediate spermatogenesis impairment 57 as well as reduced testosterone and sperm motility in high and moderate male runners 58 . Oppositely, in α1-ADRsknockout-male-mice 22 fertility and spermatogenesis are altered, suggesting the important and complex involvement of adrenergic signaling in spermatogenesis and fertility.…”
Section: Discussionsupporting
confidence: 85%
“…The CUMS is a stress model using animals to expose to different mild stressors to mimic the actual stress condition (Antoniuk et al., 2019). Indeed, the significant increase of corticosterone level in this study confirmed actual chronic stress, which was in agreement to others (Silvana & Tatjana, 2019; Zou et al., 2019). In addition, the testosterone level was significantly decreased after stress induction, implicating that CUMS interrupts steroidogenic machinery proteins such as StAR and CYP11A1 as previously described (Fahim et al., 2019; Sakr et al., 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, Fahim and coworkers (2019) have also demonstrated the degenerative seminiferous epithelium such as necrotic spermatogenic cells and some tubules shown completely empty in CUMS rats. Similar to depressed patients, low sperm qualities were observed with increased serum corticosterone levels (Hirano et al., 2014; Zou et al., 2019). It has also been demonstrated the significantly lower expressions of testicular steroidogenic proteins such as cytochrome P450 side‐chain cleavage enzyme (P450scc) and steroidogenic acute regulatory (StAR) protein in CUMS rats corroborated with the decreased testosterone levels (Sakr et al., 2015).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our day-to-day lives, stress has become an omnipresent phenomenon. Stress plays a key role in alterations in various physiological responses and can even lead to various diseases, including sub-fertility or infertility in men [10,11]. Stress has an adverse effect on endocrine function and the male reproductive system, including alterations in androgenic hormone levels, sperm maturation, and testicular function [12].…”
Section: Introductionmentioning
confidence: 99%